2009
DOI: 10.1029/2009gl037375
|View full text |Cite
|
Sign up to set email alerts
|

“Medieval Warm Period” on the northern slope of central Tianshan Mountains, Xinjiang, NW China

Abstract: “Medieval Warm Period” is used to describe a past climate epochs in Europe and neighboring regions from the ninth to the fourteenth centuries. In order to discuss the palaeoclimate changes during the MWP on the northern slope of central Tianshan Mountains in Xinjiang Autonomous Region, northwestern China, three Holocene sediment profiles in Daxigou region, Caotan Lake and Sichang Lake located in different elevations and vegetation zones were chosen for further discussion. A multi‐proxy reconstruction of the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…Pollen and phytolith records of a 175‐cm peat profile (44°25.06′ N, 86°01.26′ E) at Caotan Lake, northern Xinjiang, north‐eastern China showed that the climate was characterized by alternate periods of wet and dry conditions since 2500 cal yr bp , but the A/C pollen ratios continued to decrease. The continued decrease of A/C was not linked to climatic drying but probably reflected human disturbance at Caotan Lake (Zhang et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Pollen and phytolith records of a 175‐cm peat profile (44°25.06′ N, 86°01.26′ E) at Caotan Lake, northern Xinjiang, north‐eastern China showed that the climate was characterized by alternate periods of wet and dry conditions since 2500 cal yr bp , but the A/C pollen ratios continued to decrease. The continued decrease of A/C was not linked to climatic drying but probably reflected human disturbance at Caotan Lake (Zhang et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This record revealed warm conditions from 800 to 1400 AD (including Medieval Warm Period between 800 and 1100 AD). Therefore, the so-called MWP is manifestly diverse in different regions, and the climate may have varied in time and space during this period, as has been pointed out by Zhang et al (2009) especially in the Tibetan Plateau and Xinjiang region. However, despite such variations in MWP, it is a major climate anomaly, which provides useful palaeoclimatic information.…”
Section: Comparison With Other Sitesmentioning
confidence: 94%
“…Chen et al (2006) examined the pollen and carbonate content of sediments from Bosten Lake, and concluded that the MWP was dry in south of Xinjiang (China). Zhang et al (2009) proposed a humid climate in north Xinjiang. In a comprehensive study, Yang et al (2002) used nine separate proxy climate records derived from peat, lake sediment, ice core and tree ring and other sources to compile a single weighted temperature history for all of China spanning the past two millennia.…”
Section: Comparison With Other Sitesmentioning
confidence: 99%
“…Data in the western part of China and on the Tibetan plateau are documented by Ge et al (2006), Holmes et al (2009), andZhang et al (2009). Ge et al (2003) and Zhang et al (2008) derived the winter temperature in eastern China with emphasis on the Huang He (Yellow River) and the Yangtze catchments.…”
Section: Temperature Reconstructionsmentioning
confidence: 99%